Zoom liquid lens with switchable aperture. (April 2023) - Zhang, Ziyi; Li, Lei; Liu, Xuning; Li, Lin; Li, Yangyu
Highlights: The proposed liquid lens has characteristics of switchable aperture. The proposed liquid lens has a large optical power tunable range and excellent zoom ability than conventional zoom liquid lenses. Curvature, position displacement of the liquid-liquid interface and aperture size can be tuned by only one actuator. Abstract: A zoom liquid lens with switchable aperture is demonstrated in this paper, which consists of a lens chamber, a circular truncated cone, a limit ring and two immiscible liquids. Different from conventional zoom liquid lenses, the curvature of the liquid-liquid (L-L) interface, the position of the L-L interface and the aperture size of the proposed liquid lens can be tuned by only one actuator. Then, two problems can be solved: a larger range of optical power is realized by the switchable size of the aperture, and the zoom function can be achieved by switchable position of the aperture. Thus, the proposed zoom lens has characteristics of large optical power tunable range and excellent zoom ability with only one actuator. However, due to a single actuator, the curvature, position and aperture of the proposed lens cannot be controlled arbitrarily and individually. With a large aperture of 10 mm and a small aperture of 5 mm, the range of optical power is -43 m −1 ∼ +43 m −1, the zoom ratio reaches ∼2 × and the angular resolution is 27"7. It is promising to promote the development of a new generation of miniaturized optofluidic imaging systems.